Taxonomy, pollination biology and phylogenetic analysis of Schismatoglottis Calyptrata Complex (Schismatoglottideae: Araceae) - Hoe, Yin Chen (Universiti Malaysia Sarawak(UNIMAS), 2016)
Schismatoglottis Calyptrata complex is the most widespread complex in genus Schismatoglottis and is extremely variable in vegetative and inflorescence structures. Taxonomy, pollination biology, and phylogeny of ten species of Calyptrata complex were investigated. Eight novel species (S. adducta S.Y.Wong & Y.C.Hoe, S. baangongensis S.Y.Wong & Y.C.Hoe, S. caesia S.Y.Wong & Y.C.Hoe, S. giamensis S.Y.Wong & Y.C.Hoe, S. laxipistillata S.Y.Wong & Y.C.Hoe, S. pantiensis S.Y.Wong & Y.C.Hoe, S. pseudoniahensis S.Y.Wong & Y.C.Hoe and S. roh S.Y.Wong & Y.C.Hoe) were described; Schismatoglottis muluensis M.Hotta is resurrected and S. calyptrata (Roxb.) Zoll. & Moritzi is re-circumscribed. The main pollinator for all species of Calyptrata complex is Colocasiomyia spp. (Diptera: Drosophilidae); secondary pollinator is Cycreon sp. (Hydrophiloideae: Hydrophilidae); opportunist pollinator is Chaleonus spp. (Coleoptera: Chrysomelidae) and Parastasia spp. (Scarabaeidae: Rutelinae); visitors are Trigona sp. (Apinae: Meliponini), Pteromalidae wasps, Chironomidae flies and Atheta sp. (Staphylinidae: Aleocharinae, except as secondary pollinator in S. muluensis). The floral scent serve to attract the insects and a moderately constricted spathe trapping mechanism serve to retain the visited insects during pistillate anthesis. Gas chromatography-mass spectrometry (GC-MS) analyses revealed all investigated species of Calyptrata complex emitted ester compound class, especially the dominant compound of 3-butenoic acid, 3-methyl-, methyl ester (> 96.35 %) and small relative amount of 2-butenoic acid, 3-methyl-, methyl ester (0.09 – 0.72 %). The floral scent of different inflorescence parts (S. baangongensis, S. giamensis and S. adducta) showed the appendix emitted the highest total amount (ng/hr) and number of floral compond at period I (0600 – 0800) during pistillate anthesis, followed by spathe, staminate flower zone and pistillate flower zone. Thermogenesis is biphasic in S. adducta, S. calyptrata, S. giamensis, S. pseudoniahensis and S. roh Ar1240, with the first peak occurred during pistillate anthesis, the second was during staminate anthesis. matK gene region produced a well resolved tree topology than ITS gene region for phylogeny constructed from 21 species of Calyptrata complex. A reduced phylogeny of eleven accessions representing ten taxa based on matK gene region was used for subsequent locality, insect visitors, floral scent and morphological characters optimization. The tree partially resolved the relationship among species in Calyptrata complex. All species of the Calyptrata complex species are pollinated by Colocasiomyia flies and detected to emit 3-butenoic, 3- methyl, methyl ester and 2-butenoic acid, 3-methyl, methyl ester (except floral scent of S. pesudoniahensis is not sampled). The species of Calyptrata complex showed distinctive relationships: Schismatoglottis calyptrata which was not visited by beetles, has very few interpistillar staminodes (6 – 12); species of Calyptrata complex in Peninsular Malaysia which were visited by Chaleonus beetles, bear few interpistillar staminodes (13 – 66); species of Calyptrata complex in Sarawak, which were visited by Chaleonus beetles and Parastasia beetles (S. muluensis, S. baangongensis, S. roh Ar2445 and S. roh Ar1240), bear average to many interpistillar staminodes (80 – 469).